On the fecundity and sex-ratio of Botia Dario (Hamilton) (Cypriniformes : Cobitidae) (University Journal of Zoology, Rajshahi University, 2008)
A total of 1183 Botia Dario (Hamilton) samples were collected from Rajshahi (Shaheb Bazar, Binodpur Bazar, Talaimari Bazar, Kazla Bazar and Godagari) during the period from January, 2002 to August, 2003 to study the fecundity, sex-ratio, relationship between fecundity and total length, standard length, body weight, ovary length as well as ovary weight. The mean fecundity was calculated as 31833.50±10313.42 with a range of 5245 to 53754 in fishes ranging in total length from 96 mm to 135 mm (mean 115.50±12.11 mm) and in body weight from 14.51 g to 43.29 g (mean 29.71±6.91 g). The relationship between the fecundity (F) and total length (TL), standard length (SL), body weight (BW), ovary length (OL) and ovary weight (OW) were found to be linear with the r values 0.94, 0.94, 0.95, 0.92 and 0.98, respectively. The ovum diameter ranged from 0.3 to 0.72 mm and the mean diameter was calculated as 0.518±0.06 mm. The male to female ratio was 1:0.61. Key words: Botia dario, fecundity, sex-ratio. Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 27-29